A Bibliometric Trend Analysis of Augmented Reality in STEM Education - Dogru, M. Said; FATİH, YÜZBAŞIOĞLU; Arpacı, İbrahim (Routledge Journals, Taylor & Francis Ltd., 2025)
This study aims to uncover research trends using augmented reality (AR) technology in STEM education through content analysis and bibliometric network analysis. The bibliometric network analysis revealed that the most frequently used keywords by authors were 'augmented reality', 'STEM', and 'STEM education'. Content analysis further indicated that "educational outcomes" was the most studied variable across the articles. The most investigated sample group was college students. Regarding research methodology, approximately one-third of the studies employed qualitative methods, while another third used quantitative approaches. The content analysis findings suggest that using AR technologies in STEM education is beneficial and promising for students. Moreover, integrating AR technologies into STEM curricula enriches students' learning experiences and motivates them. Based on these results, significant recommendations are offered for educators and policymakers.
Keywords: Augmented Reality; Education; STEM